Association of Maternal Dietary Patterns With Birth Weight and the Mediation of Gestational Weight Gain: A Prospective Birth Cohort - Li, Yan; Zhou, Xuezhen; Zhang, Yu; Zhong, Chunrong; Huang, Li; Chen, Xi; Chen, Renjuan; Wu, Jiangyue; Li, Qian; Sun, Guoqiang; Yin, Heng; Xiong, Guoping; et al. (Frontiers in Nutrition, 2021)
The associations among maternal diet, birth weight and gestational weight gain are still inconclusive. This study aimed to investigate the associations between maternal dietary patterns and birth weight, and further explore whether GWG mediates these associations. A total of 3,334 pregnant women who completed a validated semi-quantitative food frequency questionnaire from the Tongji Maternal and Child Health Cohort were included. Dietary patterns were extracted by using principal component analysis. Regression models and mediation analyses were performed to explore the associations between dietary patterns and birth weight and the effects of GWG on these associations. Five dietary patterns were identified: “Beans-vegetables”, “Fish-meat-eggs”, “Nuts-whole grains”, “Organ-poultry-seafood” and “Rice-wheat-fruits”. Only women following “Beans-vegetables” pattern had heavier newborns (β=47.39; 95% CI: 12.25, 82.54). Women following “Beans-vegetables” pattern had significantly lower GWG (β=-0.70; 95% CI: -1.15, -0.25) and had a 16% lower risk of excessive GWG and 11% higher odd of adequate GWG. The association between “Beans-vegetables” pattern and birth weight was negatively mediated by GWG. A dietary pattern enriched in beans and vegetables is beneficial for effectively controlling GWG and increasing birth weight. GWG serves.